2004
DOI: 10.1002/jso.20061
|View full text |Cite
|
Sign up to set email alerts
|

Variability in axillary lymph node dissection for breast cancer

Abstract: This population-based study showed a large variation in the number of reported lymph nodes between hospitals. A more extensive surgical dissection or histopathological examination of the specimen generally resulted in a higher number of positive nodes. Although the impact of misclassification on adjuvant treatment will have varied, the impact with regard to adjuvant regional radiotherapy may have been considerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 38 publications
3
23
3
1
Order By: Relevance
“…The variation in these findings may be due to different indications to SN biopsy and other differences in the study populations, like in the proportion of screen detected cases. Also the number of examined nodes influences the detection rate of four or more positive nodes [16]. Nevertheless, the identified risk factors predicting four or more positive axillary nodes in the present study were rather similar as reported in the earlier studies [3,[13][14][15].…”
Section: Discussion the Prevalence Of Four Or More Metastastic Axillasupporting
confidence: 89%
“…The variation in these findings may be due to different indications to SN biopsy and other differences in the study populations, like in the proportion of screen detected cases. Also the number of examined nodes influences the detection rate of four or more positive nodes [16]. Nevertheless, the identified risk factors predicting four or more positive axillary nodes in the present study were rather similar as reported in the earlier studies [3,[13][14][15].…”
Section: Discussion the Prevalence Of Four Or More Metastastic Axillasupporting
confidence: 89%
“…In some studies it is stated that as the age of the patient increases, ALN number decreases (Schaapveld et al, 2004). Such relationship is not found in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…In the current staging system [10], the utility of the ANIN for predicting disease burden in the axilla is confounded by the number of nodes removed [11]. The likelihood of finding positive nodes in the axilla increases with the number of nodes dissected, and the likelihood of having residual disease in the axilla decreases with a more extensive dissection [27][28][29][30][31]. Furthermore, the extent of axillary node dissection can vary by the surgeon's preference [11].…”
Section: Discussionmentioning
confidence: 99%